Managing ‘Schizophrenia in the Midst of Schizophrenia’- the role of assertive community treatment. - Ahmad Nabil MR,; Marhani M,; Azlin B, (Penerbit UKM, 2014)
This case report emphasizes the role of Assertive Community Treatment (ACT) in managing a family with four members suffering from mental illness, mainly schizophrenia. We report a case of middle-aged lady who was diagnosed with treatment resistant schizophrenia (TRS) living with two other family members with the same illness and their carer who developed major depression from shouldering the burden of caring for mentally ill family members. ACT, through its holistic approach, proved to have reduced hospitalizations and improve symptom control and quality of life in this family.